1983
DOI: 10.1154/s0376030800016992
|View full text |Cite
|
Sign up to set email alerts
|

A Useful Guide for X-Ray Stress Evaluation (XSE)

Abstract: This paper summarizes experiences available for the measurement of lattice strains in different materials with different wavelengths to evaluate stresses by means of X-rays. The recommendations given are based on previous statements. Some principles of fundamentals of X-ray physics for the recording of interference lines with Ω and ψ-diffractometers are dealt with. Methods applicable for the determination of the peak position of the interference lines, the assessment of linear and non-linear lattice strain dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…Reviews on residual stress measurements by XRD can be found in the literature [38][39][40][41]. Diffraction is based on Bragg's law, which relates the interplanar distance of a particular hkl set of planes with the diffraction angle, θ.…”
Section: Residual Stress Measurements Using Xrdmentioning
confidence: 99%
“…Reviews on residual stress measurements by XRD can be found in the literature [38][39][40][41]. Diffraction is based on Bragg's law, which relates the interplanar distance of a particular hkl set of planes with the diffraction angle, θ.…”
Section: Residual Stress Measurements Using Xrdmentioning
confidence: 99%
“…Absorption correction, background subtraction, and Lorentz polarisation were applied [12]. Stresses were calculated according to the sin 2 ψ-method [13]. In LRS the line (λ = 457.9 nm) of an Ar + ion laser was used for excitation, a Dilor XY triple monochromator for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For residual stress determination from diffraction lineshift strain data the so-called 'sin2~k method' is well established. Review papers of the method have been given by DSlle (1979), James & Cohen (1980), Hauk (1984) and Hauk & Macherauch (1984). For texturefree materials the measured diffraction strain quite often exhibits straight-line behaviour when plotted vs sin2ff.…”
Section: Introductionmentioning
confidence: 99%
“…In practice reflections potentially useful for residual stress analysis until recently were not often used owing to overlap with other diffraction peaks. Several authors (Hauk, Oudelhoven & Vaessen, 1981;Hauk, 1984;Stuitje, 1985) have shown the practical viability of their application. It may be expected that their use for stress analysis will increase because of the availability of synchrotron and neutron radiation and also because of the advent of the position-sensitive detector (PSD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation